A brief questionnaire to assess goal orientations: development and validity - Alonso-Tapia, Jesús; Nieto, Carmen (Anales de Psicología / Annals of Psychology, 2025)
This study focuses on developing and validating a brief questionnaire to assess goal orientations and their impact on students’ perceptions of classroom motivational climate (CMC). It explores potential cultural and gender differences. The sample included 5,471 secondary school students (3,433 from Spain, 54% female; 1,946 from Costa Rica, 48.8% female). Participants completed the Brief Goal Orientation Questionnaire (BGOQ) and the Classroom Motivational Climate (CMC-Q) (Author et al., 2008). Confirmatory factor analyses and multigroup analyses were performed on samples from both countries. Results confirmed the structural validity of the questionnaire. Learning orientations were positively correlated with a learning-oriented CMC. While no significant differences were found in regression patterns between countries or genders, variations in correlations between learning and performance orientations emerged between the Spanish and Costa Rican samples. The findings indicate that the BGOQ is an effective tool for examining goal orientations. Goal orientations influence perceptions of the CMC. The study emphasizes the need to account for cultural and gender differences when researching goal orientations.